On the issue of the research development in student sports area: A review of papers for the period from 2000 to 2022 - Eremina, Ekaterina A.; Filipeva, Diana Dmitrievna; Olkhovskiy, Roman M.; Ermakova, Marina A. (Физическое воспитание и студенческий спорт, 2023)
In accordance with the Concept of Student Sport Development in the Russian Federation until 2025, one of the priority directions is the improvement of scientific and methodological support of the subjects of the student sports system. In the context of scientific and methodological support of student sport it is significant not only to intensify research in this area, but also to match the direction of the research with the key tasks of student sport development. In order to form approaches for the development of the research studies taking into account priority directions of student sports development, the authors have carried out and systematized 8083 papers on student sport and physical education of students. The papers were published in scientific journals and materials of research conferences for the period from 2000 to 2022 and placed in scientific electronic library. Based on the results of the study, the authors identified key trends in the development of scientific research activities in the field of student sports. The authors formed a model of interaction between the department of physical education and other structural units and organizations to expand the directions of scientific research.